Concerted action of the ribosome and the associated chaperone trigger factor confines nascent polypeptide folding - Hoffmann, Anja; Becker, Annemarie; Zachmann-Brand, Beate; Bukau, Bernd; Kramer, Günter (Molecular cell, 2012)
Summary: How nascent polypeptides emerging from ribosomes fold into functional structures is poorly understood. Here, we monitor disulfide bond formation, protease resistance, and enzymatic activity in nascent polypeptides to show that in close proximity to the ribosome, conformational space and kinetics of folding are restricted. Folding constraints decrease incrementally with distance from the ribosome surface. Upon ribosome binding, the chaperone Trigger Factor counters folding also of longer nascent chains, to extents varying between different chain segments. Trigger Factor even binds and unfolds pre-existing folded structures, the unfolding activity being limited by the thermodynamic stability of nascent chains. Folding retardation and unfolding activities are not shared by the DnaK chaperone assisting later folding steps. These ribosome- and Trigger Factor-specific activities together constitute an efficient mechanism to prevent or even revert premature folding, effectively limiting misfolded intermediates during protein synthesis.
Available online 23 August 2012
Gesehen am 21.06.2018